Mechanisms of an inhibitory control training to reduce binge eating behaviours: study protocol of the randomized controlled proof-of-principle MIND BINGES trial - Sebastian M. Max; Katrin E. Giel; Christian Plewnia; Simone Weller; Andreas J. Fallgatter; Veronika Lossa; Stephan Zipfel; Kathrin Schag (Journal of Eating Disorders)
Abstract Current guidelines recommend psychotherapy as first-line treatment for eating disorders. Many individuals with eating disorders characterized by binge eating episodes benefit from psychotherapy. However, a substantial subgroup does not achieve abstinence from binge eating. Bulimia Nervosa (BN) and Binge eating disorder (BED), along with other Specified/Unspecified Feeding or Eating Disorders (OSFED/UFED) with regular binge eating behaviour can be clustered on a continuum of eating disorders which is characterized by elevated impulsivity. Elevated impulsivity, and especially decreased inhibitory control, seem to be key factors in developing and maintaining binge eating behaviour. To target and modify these proposed underlying altered processes of binge eating, cognitive training approaches promise to achieve an amelioration of eating disorder-related psychopathology. Feedback is thought to play a crucial role in cognitive training approaches to increase learning and maintain motivation but its exact role has not been examined yet. MIND BINGES is a prospective, randomized controlled proof-of-principle trial investigating a food-modified inhibitory control training (ICT) and in particular the role of feedback on each individual’s performance. 63 patients with regular binge eating (BN, BED, OSFED, UFED) will be randomly assigned to receive either ICT with feedback after each session, ICT without feedback, or be assigned to a waitlist-control group (WL). The ICT is based on an antisaccade paradigm consisting of six training sessions over the course of two weeks. As the role of individual feedback provided to patients is unclear, the core aims are to investigate: (1) whether ICT without feedback is non-inferior to ICT with feedback in reducing binge eating episodes, and (2) whether ICT without feedback is superior to WL in reducing binge eating episodes. Thus, the primary endpoint is binge eating frequency in terms of changes in binge eating episodes four and 12 weeks after ICT/WL termination compared to baseline. Secondary outcomes include eating disorder psychopathology, general psychopathology, inhibitory control capacities, impulsivity, quality of life, self-esteem, and self-efficacy. Lastly, regression analyses will be conducted to explore the impact of secondary outcomes on the likelihood of a positive treatment effect. The results of the present trial will help to disentangle different elements of ICT, in particular the role of feedback. Based on the secondary outcomes, this trial might contribute to a better understanding of pathways and underlying mechanisms of an ICT. In sum, this helps developing possible individually tailored and effective treatment approaches for individuals suffering from regular binge eating. Findings might also inform cognitive trainings targeting symptoms of other mental health disorders.